Demographic and clinical factors associated with change of drug regimen due to adverse drug reactions among new tuberculosis patients in the upper north and upper northeast of Thailand: A secondary data analysis from a routine regional TB reporting system - Arunothong, Surachet; Sangsawang, Choopong; Thammawijaya, Panithee; Rattanajiamrangsri, Srisongchai; Hoothummakul, Sudjai (Biomedical Sciences and Clinical Medicine, 2024)
Objective This study aimed to identify demographic and clinical factors associated with changeof the anti-TB drug regimen due to adverse drug reactions (ADRs) among new tuberculosis (TB) patients in the upper north and upper northeast regions of Thailand. Methods A cross-sectional study was conducted among new TB patients in the areas of Disease Prevention and Control region 10 (the upper north area) from 1 Oct 2008 to 30 Sep 2013 and region 6 (the upper northeast area) from 1 Oct 2012 to 30 Sep 2013. Demographic and clinical data and the status of changing drug regimen were extracted from the Tuberculosis Clinic Management (TBCM) database. Multivariate logistic regression was used to analyze the association between change of drug regimen and the determinants. Results Records were analyzed of 26,444 and 5,982 new TB patients in the upper north and upper northeast areas of Thailand, respectively. The overall incidence of anti-TB drug regimen change due to ADRs was 2.01%. Multivariate analysis of the study population revealed factors significantly associated with this change, including old age, and being registered in the upper north area, female, human immunodeficiency virus (HIV) co-infected, an anti-retroviral drug user, separate anti-TB tablet user, and having co-morbidities with hypertension, chronic kidney disease, liver disease, and cancer. Conclusions Liver disease was a factor commonly associated with change of drug regimen due to ADRs among new TB patients in the two regional areas. Further clinical trials are needed to discover effective interventions during treatment for the prevention of ADRs among new TB patients with liver disease. Other associated factors should be monitored properly, based on this data analysis of new TB patients in each area.